2020
DOI: 10.1097/ccm.0000000000004411
|View full text |Cite
|
Sign up to set email alerts
|

Acute Physiology and Chronic Health Evaluation II Score as a Predictor of Hospital Mortality in Patients of Coronavirus Disease 2019

Abstract: Objectives: Coronavirus disease 2019 has emerged as a major global health threat with a great number of deaths in China. We aimed to assess the association between Acute Physiology and Chronic Health Evaluation II score and hospital mortality in patients with coronavirus disease 2019, and to compare the predictive ability of Acute Physiology and Chronic Health Evaluation II score, with Sequential Organ Failure Assessment score and Confusion, Urea, Respiratory rate, Blood pressure, Age 65 (CURB65) score.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
177
4
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(209 citation statements)
references
References 24 publications
19
177
4
2
Order By: Relevance
“…The co-expression of ACE2 and TMPRSS2 was reported in type 1 pneumocytes [195], alveolar macrophages [9,192], lymphocytes [9], smooth muscle cells and enterocytes in the gastrointestinal tract [9,195], vessel smooth muscle cells [9], cardiomyocytes [9,192], hepatocytes [169], kidney cells [87], proximal tubule cells [114], and neurons [112], all of which are in line with the common clinical symptoms of COVID-19 [15,19,61,151,166,183,191,197]. Single-cell RNA profiling revealed that male gender, advanced age, and smoking habit can increase the co-expression of ACE2 and TMPRESS2 Viral components are recognized by the MyD88 pathway in the endosome, leading to the releases of IL-6 and NFκB from immune cells including macrophages, monocytes, and dendrites.…”
Section: The Mechanisms Underlying Sars-cov-2 Infectionsupporting
confidence: 53%
See 2 more Smart Citations
“…The co-expression of ACE2 and TMPRSS2 was reported in type 1 pneumocytes [195], alveolar macrophages [9,192], lymphocytes [9], smooth muscle cells and enterocytes in the gastrointestinal tract [9,195], vessel smooth muscle cells [9], cardiomyocytes [9,192], hepatocytes [169], kidney cells [87], proximal tubule cells [114], and neurons [112], all of which are in line with the common clinical symptoms of COVID-19 [15,19,61,151,166,183,191,197]. Single-cell RNA profiling revealed that male gender, advanced age, and smoking habit can increase the co-expression of ACE2 and TMPRESS2 Viral components are recognized by the MyD88 pathway in the endosome, leading to the releases of IL-6 and NFκB from immune cells including macrophages, monocytes, and dendrites.…”
Section: The Mechanisms Underlying Sars-cov-2 Infectionsupporting
confidence: 53%
“…As noted above, the lungs are the organ most vulnerable to SARS-CoV-2, and importantly, respiratory failure associated with ARDS is the leading cause of death in individuals with COVID-19, contributing to 86% of the deaths [132]. In the severe or critical cases in intensive care units (ICUs), 53-95% of the patients developed ARDS [2,183,197]. Among those, 2-11% of the patients with ARDS required extracorporeal membrane oxygenation support, and the survival rate of those patients was quite low [61,166,183,191].…”
Section: Multi-organ Dysfunction/failure Respiratory Failure/ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, both neutrophils and lymphocytes were shown to have excellent predictive ability to identify severe COVID-19 disease, which was in agreement with the typical progress of virus infection. Another important nding in our study was related to platelet levels, a lower level of platelet was identi ed as an independent risk factor for severe COVID-19, which was in consistent with the study published by Zhe Zhu et.al [8]. As we know, platelets are small (2-4 µm in diameter) anucleated cells derived from megakaryocytes in bone marrow, and are responsible for maintaining the integrity of the vasculature.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, there was no association between comorbidities and clinical outcome. Another investigation reported that in COVID-19 ICU patients, APACHE II and SOFA scores were independent outcome predictors [ 23 ]. A retrospective, observational study of 85 fatal cases reported that the most common causes of death in COVID-19 ICU patients are respiratory failure (46.9%), septic shock (19.8%), multiple organ failure (16%), and cardiac arrest (8.6%).…”
Section: Discussionmentioning
confidence: 99%